The Role of Self-Compassion as A Moderating Variable : Perception of Competitiveness on The Impostor Phenomenon Among First-Year College Students - Praramadhanti, Gita Dwi; Widyasari, Pratiwi (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the moderating role of self-compassion on the relationship between the perception of a competitive environment and the impostor phenomenon in a sample of 215 first-year college students in Indonesia. The study employed a quantitative approach and the data were collected using an online questionnaire consisting of three measuring instruments: Perceived Competitiveness Questionnaire (PCQ), Clance Impostor Phenomenon Scale (CIPS), and Self-Compassion Scale (SCS). Correlation analysis and moderated regression analysis were performed to test the hypotheses of the study. This study shows that the perception of competitiveness was negatively correlated with the impostor phenomenon. Additionally, self-compassion has a significant negative correlation with feelings of being an impostor. This research also reveals that self-compassion positively moderates the relationship between the perception of competitiveness and the impostor phenomenon. These findings emphasize the importance of self-compassion as a protective factor in mitigating the negative impacts of competitive academic settings and reducing potential impostor phenomenon by empowering college students with resilience and greater confidence.